Experimental Investigation on Multiscale Fracturing in Thermally Treated Sandstone under SHPB Impact Loading - Shang Yang; Jun Wang; Zhi Zhang; Jianguo Ning; Guoqing Sun (Shock and Vibration)
To study the effect of temperature on the dynamic mechanical behaviors and fracture characteristics of thermally treated sandstone, compressive dynamic loading experiments were performed on a series of samples using a split Hopkinson pressure bar (SHPB). In the tests, the dynamic uniaxial compressive strength of the thermally treated sandstone was inversely proportional to the temperature treatment in the range of 200°C–1000°C, while the dynamic elastic modulus first increased and then gradually decreased after different temperature treatments. The results show that two classical mechanical types (i.e., Class I and Class II) are observed from the dynamic stress-strain responses of SHPB tests for thermally treated sandstone. By means of scanning electron microscopy (SEM), the microdifference of postloading microfracture characteristics in Class I and Class II behavior was identified. In Class I behavior, intercrystalline cracks (IE) are the chief form of cracks on the fracture surface of a specimen fractured by SHPB loading even though there some intracrystalline cracks may also be present. In contrast, Class II behavior results from the chief cracking type being intracrystalline cracks.